Effectiveness of Out-Class Learning at the Museum (OCAM) on Motivation and Learning Outcomes of History - Aji Saputra, Mochammad Ronaldy; Widiadi, Aditya Nugroho (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research examines whether there is a causal relationship between variables, namely Out-Class At The Museum (OCAM) learning on motivation and history learning outcomes. This research is a quantitative experimental research with a one-group pretest-posttest design. The techniques used to collect data are tests, observation sheets, and questionnaires. Data analysis was carried out descriptively and inferentially. The research results show that students' motivation and learning outcomes in class are still low. It is known that learning motivation is an average of 49.5 and learning outcomes are an average of 46 during the pretest. Then, when treated with OCAM learning, learning motivation was an average of 74, and learning outcomes were an average of 62 during the posttest. OCAM learning is effective for motivation and learning outcomes. This is known from the learning motivation variable with a value of Sig. (2-tailed) is 0.000<0.05 and the learning outcome variable has a value of Sig. (2-tailed) is 0.000<0.05, so there is a significant difference between the average pretest and posttest results.